PENGARUH PENDIDIKAN FORMAL DAN PELATIHAN TERHADAP PROFESIONALISME KEPALA SEKOLAH DASAR - Triyaningsih, SL . (Universitas Slamet Riyadi, 2006)
ABSTRACT The purpose of this research is to know the effect of formal education and treatment toward headmaster profesionalisme on State Elementary School in Ngemplak Residence, Boyolali Regency. The main problem that must be focused in: 1) is there the effect of formal education toward headmaster profesionalisme? 2)Â Is there the effect of treatment toward headmaster profesionalisme? 3)Â Is there the effect of formal education and treatment are together toward headmaster profesionalisme? 4)Â Which is the variabel of formal education and treatment is dominant toward headmaster profesionalisme?. In accordance with individual analysis (t-test), the education has a positif effect and significant toward headmaster profesionalisme. This result can show according t-test and snowed t-test (3,156) > t-table (2,040) so the first hypothesis is true. There is the effect of treatment and significant toward headmaster profesionalisme. This result can shows with individual analysis (t-test) is result t-test (2,688) > t-table (2,040) so the second hypothesis is true. There is the effect of formal education and treatment is together toward headmaster profesionalisme. This result shows in F analysis, the F-test is 8,366 > t-table (3,30) so the third hypothesis is true. The result for the fourth hypothesis is true, this result can show in t-test with result of education has t-test is bigger than treatment variable. Keywords: formal education, treatment, headmaster profesionalisme